Low-odor carpet antiskid rubber

By using low-odor carpet anti-slip glue, the existing carpet backing materials have solved the problem of poor wear resistance and anti-slip effect and contain toxic ingredients, which has improved the anti-slip performance of the carpet and extended its service life, while ensuring environmental protection and human health safety.

CN119529736APending Publication Date: 2025-02-28WUXI WANLI ADHESION MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411802475.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing carpet adhesive material has poor wear resistance and anti-slip effect, and contains toxic ingredients such as halogen and heavy metals, which is not environmentally friendly enough, affecting the service life of the carpet and human health.

Method used

Low-odor carpet anti-slip glue is used, including main glue, special particle size filler, tackifying softener, anti-aging agent, ultra-wear-resistant carbon black, white carbon black, homogenizer, additives and water. The anti-slip layer is formed through a specific preparation process to improve the anti-slip performance and service life of the carpet.

Benefits of technology

It has achieved the improvement of the anti-slip performance of the carpet, extended the service life of the carpet, improved the safety and comfort of use, and avoided the harm of toxic ingredients to human health.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529736A_ABST
    Figure CN119529736A_ABST
Patent Text Reader

Abstract

The invention provides low-odor carpet anti-skid glue which comprises an anti-skid layer pressed on the bottom surface of a carpet, and the surface of the anti-skid layer is uniformly concavely and convexly arranged; the colloid of the antiskid layer comprises the following raw materials in parts by weight: 20-40 parts of a main body rubber material, 10-20 parts of a special particle size filler, 1-5 parts of a tackifying softener, 1-5 parts of an anti-aging agent, 5-10 parts of super wear-resistant carbon black, 5-10 parts of white carbon black, 1-5 parts of a homogenizing agent, 5-10 parts of an additive and 25-40 parts of water; by adopting the main body rubber material, the material is environment-friendly, non-toxic, high in wear resistance and better in anti-skid effect, and the environment-friendly anti-skid rubber is adhered to the surface of a carpet, so that the service life of the carpet is prolonged, and the use safety and comfort of the carpet are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of carpet anti-skid glue, in particular to a low-odor carpet anti-skid glue. Background Art

[0002] As people's environmental awareness increases, saving petrochemical resources has become a development trend. Environmentally friendly, low-toxic, easily degradable, renewable resource-derived products, especially plant-based castor oil, soybean oil, coconut oil, corn oil, cottonseed oil, rice bran oil, lignin, etc. and their derivatives have replaced petrochemical products or their derivatives. It has become an important trend. With the gradual development of modern industry, waterborne polyurethane is more and more widely used, and its usage is increasing, but its production raw materials have also encountered certain crises. Most of the polyols prepared from non-renewable petrochemical resources, small molecule alcohols extracted, chain extenders, etc. are non-renewable. As petrochemical resources are mined more and more, they are becoming more and more precious. People from all walks of life have begun to consider replacing them with renewable ingredients to reduce the use of petrochemical resources. The same is true for the carpet industry in the textile field. Carpet glue, as an important application sector of waterborne polyurethane resin, is more renewable. Ordinary waterborne polyurethane emulsions have the disadvantages of using raw materials that are not environmentally friendly and non-renewable during production. The poor renewable capacity of traditional carpet glue raw materials has seriously lowered the grade of the overall waterborne polyurethane resin and does not meet the green demand for product development. This has greatly limited the application of water-based polyurethane resins in carpets, resulting in serious product homogeneity. There are many similar companies, and these low-tech products will compete to lower prices, which will hinder the promotion and development of the carpet glue industry.

[0003] As a component of the carpet, the carpet backing glue is located on the back of the carpet and is the part of the carpet that contacts the ground. The existing carpet backing glue materials have poor wear resistance and anti-skid effects. After the carpet backing glue layer is worn, it will cause damage to the carpet, affecting the service life of the carpet; the poor anti-skid effect will make it easy for the carpet to slip against the ground, which will affect the safety and comfort of use on the one hand, and will further accelerate the wear of the carpet backing glue layer on the other hand, affecting the service life of the carpet. Moreover, most carpet backing glue materials contain toxic components such as halogens and heavy metals, which are not environmentally friendly and will have adverse effects on human health during use.

[0004] In summary, the present invention provides a low-odor anti-slip adhesive for carpets to solve the above problems. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a low-odor carpet anti-slip adhesive to solve the problems that most carpet backing adhesive materials in the prior art contain toxic components such as halogens and heavy metals, are not environmentally friendly, and have adverse effects on human health during use.

[0006] A low-odor carpet anti-slip adhesive comprising:

[0007] An anti-skid layer pressed onto the bottom surface of the carpet, wherein the surface of the anti-skid layer is evenly concave and convex;

[0008] The colloid of the anti-slip layer includes the following raw materials in parts by weight:

[0009] 20-40 parts of main rubber material, 10-20 parts of special particle size filler, 1-5 parts of viscosity increasing softener, 1-5 parts of anti-aging agent, 5-10 parts of super wear-resistant carbon black, 5-10 parts of white carbon black, 1-5 parts of leveling agent, 5-10 parts of additives and 25-40 parts of water;

[0010] Wherein, the main rubber material includes polyurethane emulsion;

[0011] The preparation process includes the following steps:

[0012] Step 1: first add water into the reactor, start the stirring motor, stir the inside, add the main rubber material during the stirring process, raise the temperature to 90-95℃, and keep it warm until the main rubber material is completely mixed;

[0013] Step 2: Add the special particle size filler, disperse and stir the special particle size filler to ensure that the filler particles are evenly dispersed to obtain the basic rubber material;

[0014] Step 3: Pre-press and refine the super wear-resistant carbon black and white carbon black. After 3 minutes of pressing, add a viscosity-enhancing softener and an anti-aging agent when white smoke is produced. Then, the mixture is put into an open rubber mixer and pulled through 8 to 10 times under a roller distance of 5 to 6 mm. After the rubber surface is smooth, the mixture is sheeted, water-cooled, air-dried, and stored for 12 hours to obtain a carbon black masterbatch.

[0015] Step 4: Mix the black masterbatch with the base rubber, and add the remaining homogenizer and additives into the reactor, maintain the temperature at 80-85°C for normal polymerization reaction, raise the temperature to 88-90°C after no reflux, and keep it warm for 25-35 minutes to fully mature it, start cooling after the insulation ends, add quartz powder when it is below 82°C, add plasticizer when it is below 70°C, add preservative when it is below 50°C, seal the feed port, start vacuuming for 60-80 minutes, filter and package to obtain the anti-slip glue.

[0016] Furthermore, the additives include dispersants, wetting agents, foaming agents, foam stabilizers, bactericides and preservatives, thickeners, waterproof and oil-proof agents, and silicone oil.

[0017] Furthermore, the plasticizer is one or a mixture of naphthenic oil, paraffin oil, white oil or vacuum pump oil.

[0018] Furthermore, the antioxidant consists of antioxidant KY-405L and antioxidant SP-C, and the ratio of the antioxidant KY-405L to the antioxidant SP-C is 5:3.

[0019] Furthermore, the tackifying and softening agent is composed of 5# spindle oil and odorless tackifying resin DT-100.

[0020] Furthermore, the water is deionized water.

[0021] Furthermore, the plasticizer is one or a mixture of naphthenic oil, paraffin oil, white oil or vacuum pump oil.

[0022] Furthermore, in the step 1, the rotation speed of the stirrer is 800 to 1000 rpm, and the stirring time is 25 to 30 minutes.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention adopts the main rubber material, which is environmentally friendly and non-toxic, has high wear resistance and better anti-skid effect. The environmentally friendly anti-skid glue is adhered to the surface of the carpet, which helps to extend the service life of the carpet and improve the safety and comfort of the carpet.

[0025] 2. The anti-skid glue produced in the present invention has a very comfortable feel on the carpet pad after being coated with glue, has good anti-skid performance, and has a high strength of the coating. After long-term use, it is not easy for the glue to peel off and pollute the ground. The main glue material is 20 to 40 parts. Compared with traditional raw materials, the polyurethane emulsion can reduce the hardness of the glue layer after coating, ensuring a softer feel and comfort. The addition of a special particle size filler, compared with traditional fillers, the filler is designed with a special particle size combination, which can improve the cohesive strength of the coating and has a certain flame retardancy. By adding additives, the storage stability and coating workability of the product are guaranteed.

[0026] 3. The present invention is more odor-friendly by using bio-based water-based polyurethane, effectively avoiding the odor introduced by olefinic monomers, which makes the carpet glue unable to meet the standard requirements. In addition, the water-based polyurethane emulsion prepared by the raw materials specified in the present invention has a simpler preparation method and is easier to control in the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a flow chart of the preparation method of the present invention. DETAILED DESCRIPTION

[0028] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0029] like Figure 1As shown, the present invention provides a low-odor carpet anti-slip adhesive, comprising:

[0030] The anti-skid layer is pressed on the bottom of the carpet, and the surface of the anti-skid layer is evenly concave and convex;

[0031] The colloid of the anti-slip layer includes the following raw materials in parts by weight:

[0032] 20-40 parts of main rubber material, 10-20 parts of special particle size filler, 1-5 parts of viscosity increasing softener, 1-5 parts of anti-aging agent, 5-10 parts of super wear-resistant carbon black, 5-10 parts of white carbon black, 1-5 parts of leveling agent, 5-10 parts of additives and 25-40 parts of water;

[0033] Wherein, the main rubber material includes polyurethane emulsion;

[0034] The preparation process includes the following steps:

[0035] Step 1: first add water into the reactor, start the stirring motor, stir the inside, add the main rubber material during the stirring process, raise the temperature to 90-95℃, and keep it warm until the main rubber material is completely mixed;

[0036] Step 2: Add the special particle size filler, disperse and stir the special particle size filler to ensure that the filler particles are evenly dispersed to obtain the basic rubber material;

[0037] Step 3: Pre-press and refine the super wear-resistant carbon black and white carbon black. After 3 minutes of pressing, add a viscosity-enhancing softener and an anti-aging agent when white smoke is produced. Then, the mixture is put into an open rubber mixer and pulled through 8 to 10 times under a roller distance of 5 to 6 mm. After the rubber surface is smooth, the mixture is sheeted, water-cooled, air-dried, and stored for 12 hours to obtain a carbon black masterbatch.

[0038] Step 4: Mix the black masterbatch with the base rubber, and add the remaining homogenizer and additives into the reactor, maintain the temperature at 80-85°C for normal polymerization reaction, raise the temperature to 88-90°C after no reflux, and keep it warm for 25-35 minutes to fully mature it, start cooling after the insulation ends, add quartz powder when it is below 82°C, add plasticizer when it is below 70°C, add preservative when it is below 50°C, seal the feed port, start vacuuming for 60-80 minutes, filter and package to obtain the anti-slip glue.

[0039] As an embodiment of the present invention, the additives include dispersants, wetting agents, foaming agents, foam stabilizers, bactericides and preservatives, thickeners, waterproof and oil-proof agents, and silicone oil.

[0040] As an embodiment of the present invention, the plasticizer is one or a mixture of naphthenic oil, paraffin oil, white oil or vacuum pump oil.

[0041] As an implementation mode of the present invention, the antioxidant is composed of antioxidant KY-405L and antioxidant SP-C, and the ratio of antioxidant KY-405L to antioxidant SP-C is 5:3.

[0042] As an embodiment of the present invention, the tackifying and softening agent is composed of 5# spindle oil and odorless tackifying resin DT-100.

[0043] As an embodiment of the present invention, the water is deionized water.

[0044] As an embodiment of the present invention, the plasticizer is one or a mixture of naphthenic oil, paraffin oil, white oil or vacuum pump oil.

[0045] As an embodiment of the present invention, in step 1, the rotation speed of the stirrer is 800 to 1000 rpm, and the stirring time is 25 to 30 minutes.

[0046] The invention adopts the main rubber material, which is environmentally friendly and non-toxic, has high wear resistance and better anti-skid effect. The environmentally friendly anti-skid glue is adhered to the surface of the carpet, which is helpful to prolong the service life of the carpet and improve the safety and comfort of the carpet. The produced anti-skid glue, after being coated with glue, has a very comfortable feel on the carpet pad, good anti-skid performance, high strength of the coating, and is not easy to be peeled off and pollute the ground after long-term use. The main rubber material is 20 to 40 parts. Compared with traditional raw materials, the polyurethane emulsion can reduce the hardness of the glue layer after coating, ensuring a softer foot feel and comfort. The increase of the special particle size filler, the filler is designed with a special particle size combination compared with the traditional filler, can improve the cohesive strength of the coating, and has a certain flame retardancy. By adding additives, the storage stability and gluing workability of the product are guaranteed. By using bio-based water-based polyurethane, it is more friendly to odor, effectively avoiding the odor introduced by olefin-containing monomers, so that the carpet glue cannot meet the standard requirements. Moreover, the water-based polyurethane emulsion prepared by the raw materials defined by the invention has a simpler preparation method and a more controllable preparation process.

[0047] Embodiment 1

[0048] 20 parts of main rubber material, 10 parts of special particle size filler, 1 part of viscosity increasing softener, 1 part of anti-aging agent, 5 parts of super wear-resistant carbon black, 5 parts of white carbon black, 1 part of leveling agent, 5 parts of additives and 25 parts of water;

[0049] The preparation process includes the following steps:

[0050] Step 1: first add water into the reactor, start the stirring motor, stir the inside, add the main rubber material during the stirring process, raise the temperature to 90℃, and keep it warm until the main rubber material is completely mixed;

[0051] Step 2: Add the special particle size filler, disperse and stir the special particle size filler to ensure that the filler particles are evenly dispersed to obtain the basic rubber material;

[0052] Step 3: Press and refine the super wear-resistant carbon black and white carbon black in advance. After 3 minutes of pressing and refining, add the viscosity-enhancing softener and anti-aging agent when white smoke is generated, and enter the open rubber mixer. Pull through 8 passes under the condition of a roller distance of 5mm. After the rubber surface is smooth, it is discharged, water-cooled, air-dried, and stored for 12 hours to obtain the carbon black masterbatch.

[0053] Step 4: Mix the black masterbatch with the base rubber, and add the remaining homogenizer and additives into the reactor, maintain the temperature at 80°C for normal polymerization reaction, raise the temperature to 88°C after no reflux, and keep it warm for 25 minutes to fully mature it. After the insulation ends, start cooling down, add quartz powder when it is below 82°C, add plasticizer when it is below 70°C, add preservative when it is below 50°C, seal the feed port, start vacuuming for 60 minutes, filter and package to obtain the anti-slip glue.

[0054] Embodiment 2

[0055] 30 parts of main rubber material, 15 parts of special particle size filler, 3 parts of viscosity increasing softener, 3 parts of anti-aging agent, 8 parts of super wear-resistant carbon black, 7 parts of white carbon black, 3 parts of leveling agent, 7 parts of additives and 33 parts of water;

[0056] The preparation process includes the following steps:

[0057] Step 1: First add water into the reactor, start the stirring motor, stir the inside, add the main rubber material during the stirring process, raise the temperature to 92°C, and keep it warm until the main rubber material is completely mixed;

[0058] Step 2: Add the special particle size filler, disperse and stir the special particle size filler to ensure that the filler particles are evenly dispersed to obtain the basic rubber material;

[0059] Step 3: Pre-press and refine the super wear-resistant carbon black and white carbon black. After 3 minutes of pressing, add a viscosity-enhancing softener and an anti-aging agent when white smoke is produced. Then, the mixture is put into an open rubber mixer and pulled through 9 times under a roller distance of 6 mm. After the rubber surface is smooth, the mixture is sheeted, water-cooled, air-dried, and stored for 12 hours to obtain a carbon black masterbatch.

[0060] Step 4: Mix the black masterbatch with the base rubber, and add the remaining homogenizer and additives into the reactor, maintain the temperature at 83°C for normal polymerization reaction, raise the temperature to 89°C after no reflux, and keep it warm for 30 minutes to fully mature it. After the insulation ends, start cooling down, add quartz powder when it is below 82°C, add plasticizer when it is below 70°C, add preservative when it is below 50°C, seal the feed port, start vacuuming for 70 minutes, filter and package to obtain the anti-slip glue.

[0061] Embodiment 3

[0062] 40 parts of main rubber material, 20 parts of special particle size filler, 5 parts of viscosity increasing softener, 5 parts of anti-aging agent, 10 parts of super wear-resistant carbon black, 10 parts of white carbon black, 5 parts of leveling agent, 10 parts of additives and 40 parts of water;

[0063] The preparation process includes the following steps:

[0064] Step 1: First add water into the reactor, start the stirring motor, stir the inside, add the main rubber material during the stirring process, raise the temperature to 95°C, and keep it warm until the main rubber material is completely mixed;

[0065] Step 2: Add the special particle size filler, disperse and stir the special particle size filler to ensure that the filler particles are evenly dispersed to obtain the basic rubber material;

[0066] Step 3: Pre-press and refine the super wear-resistant carbon black and white carbon black. After 3 minutes of pressing, add a viscosity-enhancing softener and an anti-aging agent when white smoke is produced. Then, the mixture is put into an open rubber mixer and pulled through 10 times under a roller distance of 6 mm. After the rubber surface is smooth, the mixture is discharged, cooled with water, air-dried, and stored for 12 hours to obtain a carbon black masterbatch.

[0067] Step 4: Mix the black masterbatch with the base rubber, and add the remaining homogenizer and additives into the reactor, maintain the temperature at 85°C for normal polymerization reaction, raise the temperature to 90°C after no reflux, and keep it warm for 35 minutes to fully mature it. After the insulation ends, start cooling down, add quartz powder when it is below 82°C, add plasticizer when it is below 70°C, add preservative when it is below 50°C, seal the feed port, start vacuuming for 80 minutes, filter and package to obtain the anti-slip glue.

[0068] The anti-slip adhesive produced in the above Examples 1-3 was coated on the back of the carpet, and the wear resistance and friction coefficient were tested and compared with those of the traditional carpet adhesive. The test results are shown in Table 1 below.

[0069] Group Wear resistance Friction coefficient Embodiment 1 17% 0.57 Embodiment 2 16% 0.60 Embodiment 3 15 0.55 Control group 20% 0.43

[0070] Therefore, after the backing glue is applied, the carpet pad feels very comfortable, has good anti-slip performance, and has high coating strength. After long-term use, it is not easy for the glue to peel off and pollute the ground.

[0071] The embodiments of the present invention are provided for the purpose of illustration and description. Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present invention.

Claims

1. A low-odor anti-slip adhesive for carpets, characterized by: include: An anti-skid layer pressed onto the bottom surface of the carpet, wherein the surface of the anti-skid layer is evenly concave and convex; The colloid of the anti-slip layer includes the following raw materials in parts by weight: 20-40 parts of main rubber material, 10-20 parts of special particle size filler, 1-5 parts of viscosity increasing softener, 1-5 parts of anti-aging agent, 5-10 parts of super wear-resistant carbon black, 5-10 parts of white carbon black, 1-5 parts of leveling agent, 5-10 parts of additives and 25-40 parts of water; Wherein, the main rubber material includes polyurethane emulsion; The preparation process includes the following steps: Step 1: first add water into the reactor, start the stirring motor, stir the inside, add the main rubber material during the stirring process, raise the temperature to 90-95℃, and keep it warm until the main rubber material is completely mixed; Step 2: Add the special particle size filler, disperse and stir the special particle size filler to ensure that the filler particles are evenly dispersed to obtain the basic rubber material; Step 3: Pre-press and refine the super wear-resistant carbon black and white carbon black. After 3 minutes of pressing, add a viscosity-enhancing softener and an anti-aging agent when white smoke is produced. Then, the mixture is put into an open rubber mixer and pulled through 8 to 10 times under a roller distance of 5 to 6 mm. After the rubber surface is smooth, the mixture is sheeted, water-cooled, air-dried, and stored for 12 hours to obtain a carbon black masterbatch. Step 4: Mix the black masterbatch with the base rubber, and add the remaining homogenizer and additives into the reactor, maintain the temperature at 80-85°C for normal polymerization reaction, raise the temperature to 88-90°C after no reflux, and keep it warm for 25-35 minutes to fully mature it, start cooling after the insulation ends, add quartz powder when it is below 82°C, add plasticizer when it is below 70°C, add preservative when it is below 50°C, seal the feed port, start vacuuming for 60-80 minutes, filter and package to obtain the anti-slip glue.

2. The low-odor anti-slip adhesive for carpets as claimed in claim 1, characterized in that: The additives include dispersants, wetting agents, foaming agents, foam stabilizers, bactericides and preservatives, thickeners, waterproof and oil-proof agents, and silicone oil.

3. The low-odor anti-slip adhesive for carpets as claimed in claim 1, characterized in that: The plasticizer is one or a mixture of naphthenic oil, paraffin oil, white oil or vacuum pump oil.

4. The low-odor anti-slip adhesive for carpets as claimed in claim 1, characterized in that: The antioxidant consists of antioxidant KY-405L and antioxidant SP-C, and the proportion of the antioxidant KY-405L to the antioxidant SP-C is 5:

3.

5. The low-odor anti-slip adhesive for carpets as claimed in claim 1, characterized in that: The tackifying and softening agent is composed of 5# spindle oil and odorless tackifying resin DT-100.

6. The low-odor anti-slip adhesive for carpets as claimed in claim 1, characterized in that: The water is deionized water.

7. The low-odor anti-slip adhesive for carpets as claimed in claim 1, characterized in that: The plasticizer is one or a mixture of naphthenic oil, paraffin oil, white oil or vacuum pump oil.

8. The low-odor anti-slip adhesive for carpets as claimed in claim 1, characterized in that: In the step 1, the rotation speed of the stirrer is 800 to 1000 rpm, and the stirring time is 25 to 30 minutes.